Bonding and Reactivity of a μ‐Hydrido Dicopper Cation1. Issue 49 (16th October 2013) - Wyss, Chelsea M.; Tate, Brandon K.; Bacsa, John; Gray, Thomas G.; Sadighi, Joseph P.
<x xml:space="preserve">Abstract</x> A bent dicopper–hydride cation that has an N‐heterocyclic carbene supporting ligand has a Cu‐H‐Cu angle of 122° in the solid state. Density functional theory suggests an open three‐centered metal–hydrogen interaction. The hydride reacts readily with methanol and with carbon dioxide; insertion of phenylacetylene affords a gem‐dicopper vinyl complex.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>